STRUCTURE DESIGN OF TANGERANG COMMUTER LINE STATION - Agung Gani Putra Windraha, Anak
Tangerang Commuter Line Station is located at Ki Asnawi street, Pasar Anyar Tangerang, Tangerang, Banten. This building is 240 meter long which consists of three levels. This station is constructed to fullfill the demand of passengers’ movement in Tangerang City and around. Tangerang Commuter Line Station is classified as Seismic Design Category D. The structures of the station are reinforced-concrete structures with steel roof frame. The modelling of building and the roof are separated so there will be 2 structure system. The building are used special moment frame structures (SMF). And the roof used ordiary moment frame (OMF). The structure design process of Tangerang Commuter Line Station are consist of structure dilatation, modelling, structural behavior analisys, detailing of reinforced concrete, checking of steel profile capacity and design of steel elements joint. The structure is designed based on code to withstand the effects of earthquakes. Tangerang Commuter Line Station planning involve literature studies and structural modelling based on software. The dynamic analysis and structural design refer to Indonesia’s national standard, SNI 1726-2012, SNI 1727-2013, SNI 1729-2015, and SNI 2847-2013. Several engineering software are used to execute building analysis and design, including ETABS 2016 version 16.2.0 and SAP2000 version 19.0.0.